PENGARUH BEBAN KERJA DAN TEKANAN REGULASI TERHADAP STRESS KERJA DENGAN WORK LIFE BALANCE SEBAGAI VARIABEL MEDIASI PADA PEGAWAI KANTOR WILAYAH DIREKTORAT JENDERAL BEA DAN CUKAI JAWA TIMUR I - Prihandana, Herdi; Rahayu, Sri; Fitrianty, Rifda (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effects of workload and regulatory pressure on job stress, with work-life balance as a mediating variable among employees of customs and excise regional office I of east java. This study employed a quantitative approach using a survey method. The population and sample consisted of 194 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results show that workload and regulatory pressure have negative and significant effects on work-life balance. Work-life balance has a negative and significant effect on job stress. Workload and regulatory pressure have positive and significant effects on job stress. Work-life balance partially mediates the effects of workload and regulatory pressure on job stress. Workload was found to have the strongest influence on job stress. These findings indicate that workload management, simplification of regulatory demands, and strengthening work-life balance are important measures for reducing employee job stress.